Implementation of Field Trip Based Cooperative Learning Method toward Communication Skills Students - V O Narsan; S Diana; A Amprasto (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This study was conducted to determine the effect of method field trip based of cooperative learning toward student’s communication skills. This research uses the preexperiment method. Subjects consisted of 35 students. Communication skills are measured using a written test (pretest and posttest) and observation sheet. Test and observation sheet communication skills was conceived and developed based on indicators of the 21st century communications. Analysis of the written test data (pretest and posttest) in this study were analyzed by statistical tests using software Statistics Package for Social Science (SPSS) and performed manually using Microsoft Excel 2010. The observation sheet data was analyzed using calculating the percentage. The data obtained from the study reveal the application of methods field trip based cooperative learning affect the communication skills. These findings may be considered by educators knowledge in choosing teaching methods to improve the communication skills.